2007
DOI: 10.1094/pdis-91-11-1464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extended Irrigation and Host Resistance on Deoxynivalenol Accumulation in Fusarium-Infected Wheat

Abstract: Deoxynivalenol (DON) levels are not easily predicted from visual disease assessment, and it is thought likely that environmental conditions such as temperature and moisture influence DON accumulation. This field study examined the influence of environmental moisture on DON accumulation in Fusarium-infected wheat (Triticum aestivum). The effect of extended mist irrigation applied from inoculation (at anthesis) until harvest was compared with mist irrigation applied from inoculation until disease assessment (at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…This is in agreement with the study of Culler et al (2007), who reported a lower DON content in wheat from fields/plots treated with extended periods of irrigation from flowering to harvest when compared to control. Leaching of DON from spikes may occur at high rainfall (Cowger et al 2009;Gautam and DillMacky 2012), and so precipitation during grain ripening in oat may similarly impact DON accumulation in oat.…”
Section: Association Between Don Content and Weather Conditions At DIsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the study of Culler et al (2007), who reported a lower DON content in wheat from fields/plots treated with extended periods of irrigation from flowering to harvest when compared to control. Leaching of DON from spikes may occur at high rainfall (Cowger et al 2009;Gautam and DillMacky 2012), and so precipitation during grain ripening in oat may similarly impact DON accumulation in oat.…”
Section: Association Between Don Content and Weather Conditions At DIsupporting
confidence: 93%
“…The mycotoxin content in grain at harvest is variable and depends largely on the interaction of plant growth stage and weather (Hooker et al 2002;Culler et al 2007;Klem et al 2007;Cowger et al 2009;Franz et al 2009;Gourdain et al 2011;Landschoot et al 2012b;Xu et al 2013Xu et al , 2014. Weather summarisations are therefore frequently calculated within different temporal time intervals (Coakley et al 1982), fixed for the number of days (7 days, 10 days etc.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive moisture in irrigated wheat fields during flowering and early grain fill period is a favorable condition for Fusarium infection [68,69]. Nevertheless, the effect of moisture in increasing the levels of DON contamination is not consistent among published studies [69][70][71][72][73].…”
Section: Preharvest Mitigation Measures and Managementmentioning
confidence: 99%
“…DON levels are strongly influenced by host genotype as well as weather later in the grain fill period. Higher DON accumulates with extended periods of moisture post-anthesis [39,40]. However, some host genotypes react to prolonged exposure to moisture with a decrease in DON content [41].…”
Section: Fhb Reduce Wheat Yield and Qualitymentioning
confidence: 99%